DARI MITIGASI MENUJU KEBANGKRUTAN: PEMETAAN BIBLIOMETRIK KONTRIBUSI MANAJEMEN RISIKO DALAM MENCEGAH KEBANGKRUTAN PERUSAHAAN - Jannah, Lu'lu'ul; Norviana, Syahida; Nirbita, Betanika Nila; Herdianto, Jacky Ardi (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Risk management is often viewed as a key strategy to prevent corporate bankruptcy, yet the research landscape remains fragmented. This study maps the development of research on risk management and corporate financial distress using bibliometric analysis. Scopus records containing “Risk Management” and “Distress” from 2010–2025 were retrieved, yielding 106 documents, and analyzed with VOSviewer. The United States leads publication output (16 documents), followed by the United Kingdom (14). Tran, N.M. is the most prolific author (3 publications), while the University of Zilina is the most productive affiliation (4 articles). Keyword co-occurrence clustering reveals six themes: financial instruments for risk mitigation; bankruptcy determinants; risk management implementation; corporate governance; banking-sector contexts; and external factors (e.g., pandemics, religion). The results highlight the multidimensional links between risk management and distress and suggest opportunities for integrative research. This mapping also offers practical insight for firms to strengthen risk management as an early-warning and prevention mechanism against bankruptcy.